Respuesta :
At first let's multiply the second terms of the given expression. So,
(8-3i)(8+8i) = 8*8 +8*8i - 3i*8 -3i*8i
= 64 + 64i -24i -24i^2 (By multiplying)
= 64 +40i -24*(-1) (Adding the like terms and i^2=1)
=64 +40i +24 (Since (-24)*(-1)= +24)
= 88+40i (Adding the like terms).
Now the original equation is :
(8-3i) - (8-3i)(8+8i) = (8-3i)-(88+40i)
=8 - 3i -88 -40i
=(8-88)-3i -40i (By grouping the like terms)
=-80 -43i (Combine the like terms).
So, the value of the given expression is -80 -43i.